Macrophage immunometabolic reprogramming impairs tissue regeneration in type 2 diabetes zebrafish model - Junior, Leonel Witcoski; de Lima, Jordana Dinorá; Guilherme Portela de Paula, André; Bastos, Thais Sibioni Berti; Luz, Rebeca Bosso dos Santos; Bini, Israel Henrique; Severino, Matheus Brandemarte; Damasceno, Luis Eduardo Alves; Paredes, Lais Cavalieri; Girardi Somensi, Amanda; Abreu, Elaine Cristina de Almeida; Brito de Souza Santos, Lucas; et al. (Frontiers in Immunology, 2026)
IntroductionType 2 diabetes mellitus (T2D) is a metabolic disorder characterized by chronic hyperglycemia, insulin resistance, and meta-inflammation, which significantly compromise tissue regeneration. Although macrophage dysfunction is implicated in impaired wound healing in T2D, the immunometabolic mechanisms linking hyperglycemia to defective tissue repair remain incompletely understood.MethodsZebrafish larvae were exposed to hyperglycemic conditions (4% dextrose) to establish a T2D-like model. Survival, glycemic and biochemical parameters were assessed, followed by caudal fin amputation to evaluate regenerative capacity. Total (Mpeg1+) and pro-inflammatory (Mpeg1+/TNF+) macrophages were quantified in vivo using confocal microscopy. Additionally, renal-derived macrophages were differentiated ex vivo under normoglycemic or hyperglycemic conditions and analyzed for mitochondrial function, reactive oxygen species (ROS) production, glucose uptake, and glycolytic metabolism using fluorescence probes and Seahorse assays.ResultsHyperglycemia induced severe metabolic dysregulation, including a 3.5-fold increase in lactate levels and elevated glycemia, and resulted in a 50% reduction in caudal fin regeneration at 72 hours post-injury. Hyperglycemic larvae exhibited a 2.3-fold increase in pro-inflammatory macrophages at the injury site. Ex vivo, macrophages exposed to hyperglycemic conditions showed a 64% reduction in mitochondrial mass, increased mitochondrial ROS production, enhanced glucose uptake, and elevated glycolytic activity, indicating a metabolic shift toward aerobic glycolysis.DiscussionThese findings demonstrate that hyperglycemia drives immunometabolic reprogramming of macrophages, sustaining a pro-inflammatory phenotype that impairs tissue regeneration. The zebrafish T2D model provides a robust platform to investigate macrophage-driven immunometabolic mechanisms underlying defective wound healing and to explore therapeutic strategies targeting macrophage metabolism in T2D.